What Do We Talk About Now When We Talk About Segmentectomy for GGO? - Li, Hanyue; Shen, Chen; Chen, Yang; Wang, Yiyang; Zhong, Chenxi; Fang, Wentao (Frontiers in Surgery, 2022)
Segmentectomy has been considered as a compromised procedure in patients with early-stage lung cancer who could not tolerate standard lobectomy. By computed tomography (CT) screening, lung cancers are increasingly detected in earlier stages, especially those appearing as ground glass opacity (GGO)-containing lesions on CT scan. This has led to the revival of segmentectomy as an intentional procedure with the aim of curing selected patients, as GGO-containing lesions represent a special group of diseases that are relatively indolent in nature and seldom have lymphatic involvement. Limited resections, especially anatomical segmentectomy, may, thus, be helpful in reducing perioperative risks and preserving higher pulmonary function for patients while retaining similar oncological outcomes. However, clinical trials focusing specifically on the role of segmentectomy in the treatment of GGO-containing lung cancers are still lacking, especially in the minimally invasive surgery setting. Emerging evidence suggests that for such lesions, the oncological non-inferiority of segmentectomy to standard lobectomymay not be limited to lesions with a size ≤ 2 cm. More importantly, it is still unclear whether segmentectomy could indeed minimize perioperative risks and to what extent it could help preserve higher pulmonary function in good-risk patients with less extent of lung parenchyma resection. Hence, it is critical to reevaluate the efficacies of minimally invasive segmentectomy including not only oncological outcomes but also perioperative results and pulmonary function changes compared with lobectomy in good-risk patients with GGO-containing lung cancers. All these remain to be explored in future studies and robust evidence is still needed to prove that patients would indeed benefit from the combination of segmentectomy and minimally invasive surgery.